Incentive Problems in Performance-Based Online Advertising Pricing: Cost per Click vs. Cost per Action - Hu, Yu (Jeffrey); Shin, Jiwoong; Tang, Zhulei (Management Science, 2016)
The multibillion-dollar online advertising industry continues to debate whether to use the cost per click (CPC) or cost per action (CPA) pricing model as an industry standard. This paper applies the economic framework of incentive contracts to study how these pricing models can lead to risk sharing between the publisher and the advertiser and incentivize them to make efforts that improve the performance of online ads. We find that, compared with the CPC model, the CPA model can better incentivize the publisher to make efforts that can improve the purchase rate. However, the CPA model can cause an adverse selection problem: the winning advertiser tends to have a lower profit margin under the CPA model than under the CPC model. We identify the conditions under which the CPA model leads to higher publisher (or advertiser) payoffs than the CPC model. Whether publishers (or advertisers) prefer the CPA model over the CPC model depends on the advertisers’ risk aversion, uncertainty in the product market, and the presence of advertisers with low immediate sales ratios. Our findings indicate a conflict of interest between publishers and advertisers in their preferences for these two pricing models. We further consider which pricing model offers greater social welfare. This paper was accepted by J. Miguel Villas-Boas, marketing.